Undergraduate scientific education and the decline of postgraduate medical researchers in Germany? A perspective discussion and review of the literature - Stieger, Philipp; Schwoerer, Alexander Peter; Buggenhagen, Holger; Braun-Dullaeus, Rüdiger C.; Albert, Christian (Frontiers in Medicine, 2025)
The decline of postgraduate medical researchers in Germany reflects fundamental gaps in undergraduate scientific education. Scientific competence (SC)—the integrated ability to think, act, and work scientifically—underpins the academic pipeline, yet its curricular implementation in frameworks such as NKLM 2.0 (National Competency-Based Learning Objectives Catalogue Medicine) and the revised ÄApprO (Approbationsordnung für Ärzte, German Licensing regulations for doctors), remains vague. German curricula do not distinguish Stokes’s “knowledge” vs. “utility” dimensions of research, nor Kölbl’s pedagogical refinements, reducing SC to a technical adjunct rather than an inquiry-driven competence vital for clinical decision-making. Student surveys reveal broad appreciation for scientific thinking but report scant structural support for independent research. Without clear, multidimensional learning objectives and longitudinal embedding—via modular research projects, protected research time, and continuous mentorship—interest in research-oriented careers will continue to wane. We call for SC to be redefined as a core, practice-integrated pillar of medical training, transcending its current role as a curricular checkbox and securing the future of academic medicine.